Composition Portfolio, Maria Kallionpää - Kallionpaa, M (University of Oxford, 2014)
Maria Kallionpää, Dphil in Music (Composition), Faculty of Music, University of Oxford. TT 2014 Table of Contents Composition Portfolio Orchestral and Choral Works El Canto de la Guerra/The Song of War Kuru Seamar Chamber Music Works Toccata Solo Works Fantasia Raindrops El Safari de la Muerte/Le Safari de la Mort Sonnenschände – Sonnenwende CD Celestifilia, acoustic version Celestifilia, principal version, digital realisation El Canto de la Guerra/The Song of War Kuru La Safari de la Muerte/Le Safari de la Mort DVD Sonnenschände – Sonnenwende, video file Toccata, video file Supporting composition portfolio to DPhil thesis: Beyond the piano: the super instrument. Widening the instrumental capacities in the context of the piano music of the 21st century. Individual scores give instruction to performing the work.